Decentralization and Effectiveness of Regional Government: Literature Review on the Implementation of Regional Autonomy in Indonesia - Samsidar, Samsidar (Pt. Anagata Sembagi Education, 2025)
This study aims to examine the relationship between decentralization and the effectiveness of regional government in Indonesia through a qualitative approach with a literature study method. Decentralization implemented after the reform through regional autonomy policies has given broad authority to regional governments to regulate their own household affairs. Although it is expected to improve the quality of public services and locally-based development, its implementation shows mixed results. This study analyzes various scientific sources in the form of journals, academic books, policy reports, and regulations to identify patterns of success and challenges in the implementation of regional autonomy. The results of the study show that the effectiveness of regional government is greatly influenced by institutional capacity, human resource competence, regional head leadership, community participation, and the ongoing monitoring system. Some regions are able to utilize autonomy to innovate governance, but most still face structural and cultural obstacles. In addition, fiscal dependence on the central government and weak coordination between institutions are obstacles to achieving effectiveness. Therefore, strengthening regional capacity and implementing an asymmetric decentralization model are important to realize effective, accountable, and participatory governance in the era of regional autonomy.